2014
DOI: 10.1063/1.4897557
|View full text |Cite
|
Sign up to set email alerts
|

All-atom molecular dynamics calculation study of entire poliovirus empty capsids in solution

Abstract: Small viruses that belong, for example, to the Picornaviridae, such as poliovirus and foot-and-mouth disease virus, consist simply of capsid proteins and a single-stranded RNA (ssRNA) genome. The capsids are quite stable in solution to protect the genome from the environment. Here, based on long-time and large-scale 6.5 × 10(6) all-atom molecular dynamics calculations for the Mahoney strain of poliovirus, we show microscopic properties of the viral capsids at a molecular level. First, we found equilibrium rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 52 publications
7
73
0
Order By: Relevance
“…This is in contrast to water molecules that possess the ability of transiting across the capsid wall in both directions. All-atom MD simulation of poliovirus in [9] exhibits similar behaviour of molecular permeability of the poliovirus capsid. The authors concluded that the poliovirus capsid can work as semipermeable membrane.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is in contrast to water molecules that possess the ability of transiting across the capsid wall in both directions. All-atom MD simulation of poliovirus in [9] exhibits similar behaviour of molecular permeability of the poliovirus capsid. The authors concluded that the poliovirus capsid can work as semipermeable membrane.…”
Section: Discussionmentioning
confidence: 72%
“…We show that water exhibits substantial rate of exchange across the capsid's wall, while ions essentially do not permeate the wall. This make the capsid shell to function as a semipermeable membrane, the behaviour also demonstrated for other viruses [9].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…We therefore suggest a dynamic as well as a structural basis for HAP antiviral activity. A dynamic capsid is not unique to HBV, as demonstrated in studies with picornaviruses (49,65) and HIV (66). We therefore propose that small molecules that limit dynamic ensembles can serve as an effective approach to antiviral treatment.…”
Section: Discussionmentioning
confidence: 95%
“…There have been several theoretical studies that investigate the osmotic pressure of ssRNA viruses [28,31,[35][36][37]. Siber and Podgornik showed that the filled ssRNA virions exhibit a small residual negative osmotic pressure, which depends strongly on the amount of capsid charges and can be turned positive with relatively higher capsid charge [28].…”
Section: Introductionmentioning
confidence: 99%